Graphite Carbon Supported Cu 2 O / Cu nanoparticle composite material mimics enzyme, preparation method and application
Through graphite phase carbon load CU2O/CU nanoc particles composite material simulation enzyme simulation enzymes, the problem of complex and time -consuming the existing total antioxidant capacity analysis method is solved, and a simple, fast, and sensitive detection effect is achieved.
Patent Information
- Application Number
- CN202411435224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing total antioxidant capacity analysis methods have the disadvantages of expensive, complex, specialized and time-consuming instruments, making it difficult to achieve simple, fast and sensitive detection.
Use graphite phase carbon load CU2O/CU nano-granular composite material simulation enzyme. By mixing sodium hydroxide and 2,3-pyrazine di carboxylic acid to form a first solution, copper nitrate and pyrazine are mixed to form a second solution, and then The two are mixed and stirred, collecting sediments for washing and drying, and eventually preparing simulation enzymes by burning.
This simulation enzyme has good catalytic activity of peroxide -like samples, can detect total antioxidant capabilities quickly and high -sensitivity, avoid the complexity and time consumption of existing methods, and reduce the detection cost.
Smart Images

Figure CN118949984B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of enzyme simulation, and in particular to a graphite phase carbon-loaded Cu2O / Cu nanoparticle composite material enzyme simulation, a preparation method and application thereof. Background Art
[0002] Excessive production of free radicals leads to oxidative stress, causing cell damage and even increasing the incidence of cardiovascular disease, diabetes, neurodegenerative diseases and other diseases. Antioxidants play an important role in reducing free radicals and resisting oxidative stress. However, most antioxidants cannot be synthesized by the human body and must be taken from external food or nutrients. Therefore, the quantitative analysis of antioxidants in food or nutritional supplements has become increasingly important for improving dietary structure and maintaining oxidative homeostasis. Considering the diversity of antioxidant components in food or nutrients, total antioxidant capacity (TAC) is recommended as a comprehensive parameter for evaluating the total activity of all antioxidants. Ascorbic acid (AA) is an important antioxidant commonly used in total antioxidant capacity analysis and is often used as a model antioxidant. Ascorbic acid equivalent is an important unit in total antioxidant capacity analysis. At present, there are many methods for total antioxidant capacity analysis or ascorbic acid detection, such as electrochemical method, fluorescence method, and high performance liquid chromatography. Although these methods have high sensitivity and reliability, they also have disadvantages such as expensive instruments, complexity, specialization, and time-consuming, which limit the practical application of these methods. To overcome these limitations, the development of a simple, rapid, and sensitive method to detect total antioxidant capacity is essential.
[0003] Colorimetric sensors are a class of analytical methods that use color changes as signal readouts. Colorimetric sensors have attracted widespread attention in total antioxidant capacity analysis due to their simple operation and low cost. The representative principle of colorimetric sensors for total antioxidant capacity analysis is based on the competition mechanism between oxidizable chromogenic substrates and antioxidants. In this case, the enzyme that catalyzes the oxidation reaction of the substrate plays a very critical role. Natural enzymes, such as laccase and horseradish peroxidase, are widely used in total antioxidant capacity analysis, but they have poor stability, high cost, and harsh conditions for use. Nanozymes are a class of nanomaterials with enzyme properties that can catalyze enzyme substrates under physiological or extreme conditions and have enzymatic reaction kinetics similar to natural enzymes. They can be used as substitutes for enzymes to construct innovative analytical methods. Copper ions play a vital role as a component of many natural enzymes. Researchers have designed and synthesized a variety of copper-based nanomaterials with enzyme-like activities, commonly known as copper-based nanozymes.
[0004] However, the aggregation of copper-based catalysts during preparation or catalytic process hinders their catalytic activity to a certain extent. Therefore, it is urgent to find a suitable carrier to prevent the aggregation of catalysts. Summary of the invention
[0005] In view of the above situation, the main purpose of the present invention is to propose a graphite phase carbon loaded Cu2O / Cu nanoparticle composite material mimicking enzyme and its preparation method and application, so as to solve the above technical problems.
[0006] The present invention provides a method for preparing a graphite phase carbon-loaded Cu2O / Cu nanoparticle composite material mimicking enzyme, the method comprising the following steps:
[0007] Adding water to sodium hydroxide and 2,3-pyrazinedicarboxylic acid to form a first solution;
[0008] adding copper nitrate and pyrazine to water to form a second solution;
[0009] mixing the first solution and the second solution and stirring;
[0010] After the stirring is completed, the precipitate is collected, and the precipitate is washed and dried in sequence to obtain layered CPL-1;
[0011] The layered CPL-1 is calcined, and after the calcination is completed, the product is collected to obtain a simulated enzyme.
[0012] The present invention also provides a graphite phase carbon-loaded Cu2O / Cu nanoparticle composite material mimic enzyme, wherein the mimic enzyme is prepared by the above-mentioned preparation method.
[0013] The present invention also proposes an application of a graphite phase carbon loaded Cu2O / Cu nanoparticle composite material to simulate enzymes. The graphite phase carbon loaded Cu2O / Cu nanoparticle composite material to simulate enzymes is used to measure antioxidant capacity.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. Prepared by simply calcining layered CPL-1. The organic ligands of CPL-1 decompose to form graphene phase carbon (gC) after calcination, and the formed Cu2O / Cu nanoparticles are orderly dispersed on gC. gC not only inhibits the aggregation of nanoparticles and prevents the decrease of nanoparticle activity, but also improves the electron transfer efficiency, thereby synergistically enhancing the catalytic activity.
[0016] 2. The porous structure of CPL-1 is retained after calcination, which improves the contact efficiency with the reactants. The synthesized mimetic enzyme has good peroxidase-like catalytic activity, which can catalyze the decomposition of hydrogen peroxide to generate hydroxyl radicals (·OH), thereby oxidizing colorless TMB to generate blue oxidized TMB. When antioxidants are present, the antioxidants consume hydroxyl radicals and hinder the color change of the total antioxidant capacity color development system. Therefore, the mimetic enzyme is used for high-sensitivity evaluation of total antioxidant capacity.
[0017] 3. The present invention not only provides a new strategy for the rapid evaluation of total antioxidant capacity, but also provides new ideas for the design of new mimetic enzymes.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description or learned through embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the reaction mechanism of the peroxidase activity of gC@Cu2O / Cu NPs prepared in the present invention and the detection mechanism of the total antioxidant capacity;
[0020] Figure 2 This is an electron microscope image of gC@Cu2O / Cu NPs prepared in Example 1 of the present invention;
[0021] Figure 3 XRD spectrum of gC@Cu2O / Cu NPs prepared in Example 1 of the present invention;
[0022] Figure 4 The UV-visible absorption spectrum of gC@Cu2O / Cu NPs catalyzed TMB / H2O2 reaction and other control experimental figures;
[0023] Figure 5 It is the pH optimization curve of the effect of pH on AA detection;
[0024] Figure 6 This is the steady-state kinetic analysis diagram of gC@Cu2O / Cu NPs.
[0025] Figure 7 It is the linear relationship between the AA concentration in the range of 30 ~ 650 μM and the absorbance at 652 nm;
[0026] Figure 8 Selectivity diagram of gC@Cu2O / Cu NPs against several common ions and biomolecules as interfering substances. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0028] These and other aspects of the embodiments of the present invention will be apparent with reference to the following description and accompanying drawings. In these descriptions and accompanying drawings, some specific implementations of the embodiments of the present invention are specifically disclosed to represent some ways of implementing the principles of the embodiments of the present invention, but it should be understood that the scope of the embodiments of the present invention is not limited thereto.
[0029] Example 1
[0030] A method for preparing a graphite-phase carbon-loaded Cu2O / Cu nanoparticle composite material mimicking enzyme, the method comprising the following steps:
[0031] 2 g of sodium hydroxide and 4.215 g of 2,3-pyrazinedicarboxylic acid were added to 500 mL of water to form a first solution;
[0032] 6.15 g of copper nitrate and 20.25 g of pyrazine were added to 500 mL of water to form a second solution;
[0033] The first solution and the second solution were mixed and stirred at room temperature for 3 h;
[0034] After stirring, a blue precipitate was obtained, which was collected and washed three times with ultrapure water, and then vacuum dried at 119.85°C to obtain layered CPL-1;
[0035] The layered CPL-1 was heated to 600 °C at a rate of 2 °C / min and maintained for 2 h for calcination. After the calcination was completed, a black powder was obtained. The product was collected to obtain a simulated enzyme, which was recorded as gC@Cu2O / Cu NPs.
[0036] Example 2
[0037] A method for preparing a graphite-phase carbon-loaded Cu2O / Cu nanoparticle composite material mimicking enzyme, the method comprising the following steps:
[0038] 1.95 g of sodium hydroxide and 3.95 g of 2,3-pyrazinedicarboxylic acid were added to 500 mL of water to form a first solution;
[0039] 5.95 g of copper nitrate and 20.05 g of pyrazine were added to 500 mL of water to form a second solution;
[0040] The first solution and the second solution were mixed and stirred at room temperature for 4 h;
[0041] After stirring, a blue precipitate was obtained, which was collected, washed twice with ultrapure water, and then vacuum dried at 110°C to obtain layered CPL-1;
[0042] The layered CPL-1 was heated to 600°C at a rate of 1°C / min and maintained for 2 hours for calcination. After the calcination was completed, a black powder was obtained. The product was collected to obtain a simulated enzyme.
[0043] Example 3
[0044] A method for preparing a graphite-phase carbon-loaded Cu2O / Cu nanoparticle composite material mimicking enzyme, the method comprising the following steps:
[0045] 2.15 g of sodium hydroxide and 4.35 g of 2,3-pyrazinedicarboxylic acid were added to 500 mL of water to form a first solution;
[0046] 6.25 g of copper nitrate and 20.45 g of pyrazine were added to 500 mL of water to form a second solution;
[0047] The first solution and the second solution were mixed and stirred at room temperature for 5 h;
[0048] After stirring, a blue precipitate was obtained, which was collected and washed five times with ultrapure water, and then vacuum dried at 125°C to obtain layered CPL-1.
[0049] The layered CPL-1 was heated to 600°C at a rate of 3°C / min and maintained for 2 hours for calcination. After the calcination was completed, a black powder was obtained. The product was collected to obtain a simulated enzyme.
[0050] Example 4
[0051] A graphite phase carbon-loaded Cu2O / Cu nanoparticle composite material simulated enzyme, wherein the simulated enzyme is prepared by adopting the above-mentioned preparation method.
[0052] Example 5
[0053] The invention discloses an application of a graphite phase carbon loaded Cu2O / Cu nanoparticle composite material simulating enzyme, which adopts the above simulating enzyme and is used for antioxidant capacity determination.
[0054] Preferably, the method for using the mimetic enzyme for antioxidant capacity determination comprises the following steps:
[0055] The mimetic enzyme prepared in Example 1 was dispersed in ultrapure water and subjected to ultrasonic treatment for 5 min to uniformly disperse the mimetic enzyme to obtain a third solution with a mimetic enzyme concentration of 1.5 mg / mL;
[0056] 50 μL of the third solution, 50 μL of TMB and 50 μL of H2O2 were added to an acetate buffer (pH = 4.6) to obtain a working solution with a total volume of 250 μL, and the desired assay sample was added and shaken at 37°C for 2 min;
[0057] After the reaction was completed, the absorbance at 652 nm was measured using a UV-visible spectrophotometer to complete the antioxidant capacity determination.
[0058] See also Figure 1 The gC@Cu2O / Cu NPs prepared by the present invention have good peroxidase-like catalytic activity, which can catalyze the decomposition of hydrogen peroxide to generate hydroxyl radicals (·OH), thereby oxidizing colorless TMB to generate blue oxidized oxTMB. When an antioxidant is present, the antioxidant consumes hydroxyl radicals and hinders the color change of the total antioxidant capacity color development system. Therefore, gC@Cu2O / Cu NPs are used for high-sensitivity evaluation of total antioxidant capacity.
[0059] The following experiments take the gC@Cu2O / Cu NPs prepared in Example 1 as an example;
[0060] Characterization of gC@Cu2O / Cu NPs:
[0061] Figure 2 The transmission electron microscopy (TEM) images in Figures a and b clearly show the nanosheet structure of gC@Cu2O / Cu NPs, which is consistent with the precursor CPL-1. Figure 2 In the high-resolution transmission electron microscopy (HRTEM) image of Figure c, lattice fringes with a d=0.215 nm were observed, which coincided with the (200) plane of cubic Cu2O, confirming that the nanosheets were Cu2O. At the same time, lattice fringes with an interlayer spacing of 0.208 nm were also observed, corresponding to the (111) plane of copper. In addition, in the XRD pattern ( Figure 3 ) shows the presence of graphitic carbon.
[0062] Feasibility verification:
[0063] In order to verify the catalytic activity of the gC@Cu2O / Cu NPs prepared in Example 1, a typical catalytic oxidation system TMB-H2O2 system was used. The specific steps are as follows: 50 μL of the third solution, 50 μL of TMB, and 50 μL of H2O2 were added to an acetate buffer solution (pH=4.6) and shaken at 37°C for 2 min to obtain a working solution with a total volume of 250 μL. The ultraviolet absorption spectrum of the working solution was measured and its absorbance at 652 nm was recorded to verify that the synthesized gC@Cu2O / Cu NPs had catalytic activity.
[0064] like Figure 4 As shown, curve a: TMB + H2O2 + gC@Cu2O / Cu NPs, curve b: TMB + gC@Cu2O / CuNPs, curve c: H2O2 + gC@Cu2O / Cu NPs, curve d: TMB + H2O2. Figure 4 It can be seen that when the TMB-H2O2 system contains gC@Cu2O / Cu NPs, a clear absorption band can be observed at 652nm. However, in the absence of gC@Cu2O / Cu NPs, the UV-visible absorption spectrum does not change significantly. The above results indicate the peroxidase-like activity of gC@Cu2O / Cu NPs.
[0065] pH Effect:
[0066] In order to improve the catalytic efficiency, the experimental conditions were optimized. Figure 5 As shown in the figure, when the pH value changes between 3 and 7, the absorbance value increases first and then decreases with the pH value, and the absorbance value is the largest at pH 4.6. Therefore, pH 4.6 was selected in subsequent experiments.
[0067] Steady-state kinetics of gC@Cu2O / Cu NPs:
[0068] In addition to changing the concentrations of TMB and H2O2, the other steps of the steady-state kinetic experiment are consistent with the above. In the kinetic experiment, when the TMB concentration is fixed at 1.2 mM, the H2O2 concentration varies between 5 and 30 mM, and when the H2O2 concentration is fixed at 20 mM, the TMB concentration varies between 0.2 and 0.7 mM. After the reaction is completed, the UV absorption spectrum of the mixed solution is measured. Finally, according to the Michaelis-Menten equation, the reaction kinetic parameters are derived and calculated as:
[0069] ;
[0070] in, represents the maximum reaction rate, represents the substrate concentration, represents the Michaelis constant.
[0071] To further investigate the POD-like activity of gC@Cu2O / Cu NPs, steady-state kinetic experiments were performed. TMB was used as the substrate and the Michaelis-Menten equation was used to evaluate the kinetic parameters. Figure 6 The Michaelis-Menten curve shown in (A) and Figure 6 The Lineweaver-Burk curve shown in (B). Figure 6 As shown in Figure 2, TMB has an influence on the K of gC@Cu2O / Cu NPs. m About 0.15 mM. K mThe lower the K, the stronger the affinity of gC@Cu2O / Cu NPs to the substrate. Compared with horseradish peroxidase (HRP), gC@Cu2O / Cu NPs has a lower K m value, indicating that it has excellent POD-like catalytic performance.
[0072] Linear relationship:
[0073] Based on the POD-like catalytic activity of gC@Cu2O / Cu NPs, its application in the detection of total antioxidant capacity was explored. In the absence of antioxidants, gC@Cu2O / Cu NPs catalyzed the decomposition of hydrogen peroxide to generate ·OH, which then oxidized TMB to oxTMB, and the color changed from colorless to blue. However, when an antioxidant was present, it reacted with gC@Cu2O / Cu NPs, thereby reducing the oxidation of TMB and preventing the solution from changing color. Figure 7 As shown in Figure 2, with the addition of antioxidants, the absorbance of the reaction solution at 652 nm decreased significantly. In the range of 30 – 650 μM, ΔA 652 Absorbance change (ΔA 652 =A1-A2, where A1 and A2 represent the absorbance values in the presence and absence of ascorbic acid in the gC@Cu2O / Cu NPs-TMB-H2O2 reaction system, respectively) and the ascorbic acid (AA) concentration. The detection limit was calculated to be 14.03 μM, which is lower than other methods using nanozymes (including copper-based nanozymes).
[0074] Selective testing:
[0075] In addition, to verify the selectivity of this method, several common ions and biomolecules were selected as interfering substances, including K + 、Na + , Cu 2+ , citric acid (CA), fructose (Fru), glutamic acid (Glu), lysine (Lys) and histidine (His). The experiment followed the same procedure and conditions as the AA analysis. The standard concentration of all interfering substances was 6.5 mM, which is equivalent to 10 times the concentration of AA (650 μM). Figure 8 As shown in the figure, the addition of AA caused a significant change in the absorbance value, while other interfering substances had relatively little effect on the absorbance value. These results indicate that non-antioxidants produce minimal interference in this method.
[0076] Actual sample testing:
[0077] In order to verify the potential application of this method, ascorbic acid was selected as a standard additive because ascorbic acid is one of the important antioxidants and its concentration equivalent is often used as a unit for determining total antioxidant capacity. First, honey was diluted 200 times with ultrapure water, and 50 μL of the resulting sample was added to the working solution prepared in Example 5. After the reaction was completed, the absorbance at 652 nm was measured and substituted into the linear equation to determine the ascorbic acid concentration. In order to verify the accuracy of the analysis, the standard addition method was used. Different concentrations of ascorbic acid were added to the sample solution, the absorbance was recorded, and the recovery was calculated. The equivalent ascorbic acid concentration was used as the unit of total antioxidant capacity, and the spike recovery method was used to verify the accuracy of the present invention. As shown in Table 1, the recovery rate was between 98.6% and 102.0%, indicating that this method has the ability to evaluate total antioxidant capacity in actual samples.
[0078] Table 1: Detection and analysis of total antioxidant capacity in honey samples
[0079]
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a graphite-phase carbon-supported Cu2O / Cu nanoparticle composite material for mimicking enzyme, characterized in that: The method comprises the following steps: Adding water to sodium hydroxide and 2,3-pyrazinedicarboxylic acid to form a first solution; adding copper nitrate and pyrazine to water to form a second solution; mixing the first solution and the second solution and stirring; After the stirring is completed, the precipitate is collected, and the precipitate is washed and dried in sequence to obtain layered CPL-1; The layered CPL-1 was calcined, and after the calcination was completed, the product was collected to obtain the mimetic enzyme, which was recorded as gC@Cu2O / CuNPs; Wherein, in the first solution, the amount of sodium hydroxide added is 1.95-2.15 g, the amount of 2,3-pyrazinedicarboxylic acid added is 3.95-4.35 g, and the amount of water added is 500 mL; in the second solution, the amount of copper nitrate added is 5.95-6.25 g, the amount of pyrazine added is 20.05-20.45 g, and the amount of water added is 500 mL; The first solution and the second solution are mixed and stirred at room temperature for 3-5 hours. The precipitate is dried under vacuum at 110-125°C. The layered CPL-1 is calcined by heating to 600°C at a rate of 1-3°C / min and maintained for 2 hours.
2. The method for preparing the graphite phase carbon supported Cu2O / Cu nanoparticle composite material enzyme mimic according to claim 1, characterized in that: During the washing process of the precipitate, ultrapure water is used for washing, and the washing times are 2-5 times.
3. A graphite phase carbon-supported Cu2O / Cu nanoparticle composite material simulating enzyme, characterized in that: The mimetic enzyme is prepared by the preparation method according to any one of claims 1 to 2.
4. An application of a graphite phase carbon-supported Cu2O / Cu nanoparticle composite material to simulate enzymes, using the graphite phase carbon-supported Cu2O / Cu nanoparticle composite material to simulate enzymes as claimed in claim 3, characterized in that: The graphite phase carbon-loaded Cu2O / Cu nanoparticle composite material simulates enzymes and is used for antioxidant capacity determination; Among them, the method corresponding to the use of the simulated enzyme for antioxidant capacity determination has the following steps: dispersing the simulated enzyme in ultrapure water, and performing ultrasonic treatment to uniformly disperse the simulated enzyme to obtain a third solution; The third solution, TMB, H2O2 and acetate buffer are prepared as a working solution, and then the desired test sample is added to perform shaking operation; After the reaction was completed, the absorbance at 652 nm was measured using a UV-visible spectrophotometer to complete the antioxidant capacity determination; In the third solution, the concentration of the mimetic enzyme was 1.5 mg / mL; The ultrasonic treatment time was 5 min; The total volume of the working solution was 250 μL, of which the third solution was added in an amount of 50 μL, TMB was added in an amount of 50 μL, H2O2 was added in an amount of 50 μL, and the pH of the acetate buffer was 4.6; During the shaking operation, the temperature was 37°C and the shaking time was 2 min.